The Factors Of Anemia Among Pregnant Women At Jaraga Sasameh Buntok Hospital In 2016 - Fakhruddin Razy; Novalia Widiya Ningrum; Norhayati Norhayati (Universitas Sari Mulia, 2018)
Background: Anemia in pregnant women can cause postpartum hemorrhage because of less Hb levels can affect the working of the uterus muscles and affect to contractions during labor. The case of pregnancy anemia ranges between 20% to 89% by setting Hb 11g% (g / dl) as its base. From the results of conducted preliminary studies at the Regional Hospital in Jaraga Sasameh Buntok obtained the data for mothers with anemia in 2014 amounted to 26.2% increasing in 2015 to 29.6%.Research Purposes: This study aims to identify the factors that affect anemia in pregnant women at the Regional Hospital in Jaraga Sasameh Buntok 2016Research Methods: This research using analytical survey method by a cross sectional design. The subjects of this study were the total number of initial visits of pregnant women (K1) at the Regional Hospital in Jaraga Sasameh Buntok as many as 453 with a sample of 82 cases. The sampling technique is determined by using a simple random technique. The collection of data obtained through secondary data by using the checklist, and this study used univariate and bivariate analysis.Research Result: From the results of chi-square test found that age pÂ factor = 0,000 and Î± value = 0.05 p Î±, parity factor obtained p value = 0.000 and Î± value = 0,05 p Î±, nutritional status factor obtained p value = 0.000 and Î± value = 0,05 p Î±, educational factor obtained p value = 0,000 and Î± value = 0,05 p Î±. Conclusion: Based on the results of research can be concluded that all variables studied have a significant relationship to the case of anemia in pregnant women.Â Keywords : Case of anemia, age, parity, education, nutritional status.